Answer:
x + 3
Step-by-step explanation:
Since we have a common denominator, we can just simply combine the numerator which is just x+3.
F(x+2)-2 is the correct answer. I got it right on my test. Just make sure the point passing through is -1,-2 or you will miss this question. Hope I help you all.
The answer is 2 candies per person per month
(1) Find the amount of candy consumed <span>per person per year:
6 700 000 000 </span>÷ 305 000 000 = 21.97 candies per person per year
(2) Find the amount of candy consumed per person per month:
1 year has 12 months.
21.97 candy per person per year ÷ 12 = 1.83 ≈ 2 candies per person per month
Yes.
9m-3m=1+19
6m=20
m=20/6=10/3
Answer:
<h3>
ln (e^2 + 1) - (e+ 1)</h3>
Step-by-step explanation:
Given f(x) = ln and g(x) = e^x + 1 to get f(g(2))-g(f(e)), we need to first find the composite function f(g(x)) and g(f(x)).
For f(g(x));
f(g(x)) = f(e^x + 1)
substitute x for e^x + 1 in f(x)
f(g(x)) = ln (e^x + 1)
f(g(2)) = ln (e^2 + 1)
For g(f(x));
g(f(x)) = g(ln x)
substitute x for ln x in g(x)
g(f(x)) = e^lnx + 1
g(f(x)) = x+1
g(f(e)) = e+1
f(g(2))-g(f(e)) = ln (e^2 + 1) - (e+ 1)